2017
DOI: 10.1007/s00296-017-3887-y
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage oligomeric protein, matrix metalloproteinase-3, and Coll2-1 as serum biomarkers in knee osteoarthritis: a cross-sectional study

Abstract: Biochemical markers reflecting joint remodeling in osteoarthritis (OA) are a promising diagnostic tool. The aim of this study was to investigate serum levels of candidate biomarkers in subjects with and without knee OA and assess their correlation with clinical parameters and knee structural damage. 56 patients with primary knee OA and 31 healthy controls participated in this study. Patients were separated into two groups: isolated knee OA and generalized OA. Clinical parameters were obtained by validated self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
31
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 35 publications
10
31
1
Order By: Relevance
“…Also, the increase in SF COMP levels correlated with the length of time post injury, suggesting that COMP may be a suitable marker for longitudinal studies to evaluate its role in joint healing [ 28 ]. Georgiev et al observed higher serum COMP levels in knee OA patients when compared to controls, and COMP correlated positively with Whole-Organ MRI Score, suggesting that COMP may reflect structural damage of the knee joint [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the increase in SF COMP levels correlated with the length of time post injury, suggesting that COMP may be a suitable marker for longitudinal studies to evaluate its role in joint healing [ 28 ]. Georgiev et al observed higher serum COMP levels in knee OA patients when compared to controls, and COMP correlated positively with Whole-Organ MRI Score, suggesting that COMP may reflect structural damage of the knee joint [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Proinflammatory cytokines, such as interleukin-1 (IL-1) and tumor necrosis factor-alpha (TNF-α), are produced by activated synoviocytes, chondrocytes and mononuclear cells, upregulate the expression of matrix metalloproteinases (MMPs) and degrade the cartilage matrix [8]. Various biomarkers, including inflammatory markers (IL-1β and TNF-α), MMPs, and matrix degradation markers (cartilage oligomeric matrix protein (COMP), C-terminal cross-linking telopeptide of type II collagen (CTX-II), and N-terminal type I collagen telopeptide), can be used to detect OA progression [9][10][11]. COMP is a 535-kDa non-collagenous protein related to the thrombospondin family and is primarily found in the articular cartilage, tendons, and synovium [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we suggest that YKL-40 may be a useful biomarker of disease activity and may be used to assess treatment towards remission, as compared to COMP.Metabolites 2020, 10, 61 2 of 11 remodeling, manifested by significant changes of the circulating markers of cartilage turnover, including total glycosaminoglycans (GAGs) and their particular types such as keratan sulphate, chondroitin sulphate, hyaluronic acid, as well as chondroitin sulphate 846 epitope [5][6][7][8].Among ECM components, which are indicators of the cartilage breakdown, there are also listed components synthesized by chondrocytes, i.e., cartilage oligomeric matrix protein (COMP) as well as human cartilage glycoprotein 39 (YKL-40), that are so far not evaluated in JIA patients. The first one is a non-collagenous glycoprotein, binding to aggrecan; fibronectin; and collagen types I, II, and IX, which seem to play a role in the structure of fibrils and in maintenance of the collagen network [9,10]. Whereas YKL-40, a glycoprotein associated with inflammation and tissue remodeling, is produced by joint tissues and recognized as a candidate autoantigen in rheumatoid arthritis.…”
mentioning
confidence: 99%
“…It has been shown that YKL-40 binds to some important components in the cartilage extracellular matrix, i.e., proteoglycans and collagens, influencing their production and assembly [11][12][13][14]. Several authors have investigated the relationship between circulating COMP or YKL-40 and the condition of articular cartilage in adult patients with and without any rheumatic disease [9][10][11][12][13][14][15][16][17][18][19]. A correlation between the degree of articular cartilage degradation expressed by COMP level but not by YKL-40 and the adipose tissue content has been observed in the patients [15].…”
mentioning
confidence: 99%
See 1 more Smart Citation